2021
DOI: 10.1016/j.omtm.2021.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of a degron reduces levels of undesired inteins after AAV-mediated protein trans-splicing in the retina

Abstract: Split intein-mediated protein trans- splicing expands AAV transfer capacity, thus overcoming the limited AAV cargo. However, non-mammalian inteins persist as trans- splicing by-products, and this could raise safety concerns for AAV intein clinical applications. In this study, we tested the ability of several degrons to selectively decrease levels of inteins after protein trans- splicing and found that a version of E. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…The excised inteins bioproduct could raise immunological concerns as it is non‐mammalian; however, no apparent toxicity has been observed in previous studies (Chen et al , 2007 ; Zhu et al , 2010 , 2011 , 2013 ; Tornabene et al , 2019 ) nor in ours, though our study was not designed to assess potential toxicity. Independently, we have recently incorporated a degron in the AAV‐intein vectors that results in selective intein degradation following PTS, therefore without significantly impacting on levels of full‐length protein (Tornabene et al , 2021 ). This could be incorporated in the future in the AAV‐N6 intein vectors, if necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The excised inteins bioproduct could raise immunological concerns as it is non‐mammalian; however, no apparent toxicity has been observed in previous studies (Chen et al , 2007 ; Zhu et al , 2010 , 2011 , 2013 ; Tornabene et al , 2019 ) nor in ours, though our study was not designed to assess potential toxicity. Independently, we have recently incorporated a degron in the AAV‐intein vectors that results in selective intein degradation following PTS, therefore without significantly impacting on levels of full‐length protein (Tornabene et al , 2021 ). This could be incorporated in the future in the AAV‐N6 intein vectors, if necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, except for the aged mice, we evaluated mice at a single time point during the retinal degeneration, which does not account for additional physiological changes that may occur as the disease starts to progress. Future longitudinal studies could shine light onto the long-term stability and biological tolerance for the DHFR DD, although a recent study analyzed mice subretinally injected with an AAV encoding for a mini DHFR degron without any apparent detriment out to 1 year of age ( Tornabene et al., 2021 ). In addition, a more thorough examination of whether particular retinal cell types are recalcitrant to DHFR DD regulatability or whether signal from readily transduced/numerous cells masks the signals from less abundant/less transduced cell types are important aspects to consider.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, lipofuscin was observed to accumulate in the retinal pigmented epithelium of the vehicle-treated Abca4 −/− mice. In contrast, there was a significant reduction in lipofuscin, in addition to improvement in other phenotypes for the mice treated with ABCA4-split intein after 3 months ( Tornabene et al, 2021 ). Similarly, studies with the retina of pig and human retinal organoids also showed improvement for the ABCA4-split-intein group compared with the vehicle controls ( Tornabene et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…ABCA4 is involved in the clearance of photoisomerized all-trans-retinal from the photoreceptor disk lumen. Mutated ABCA4 results in a buildup of lipofuscin pigments in the retinal pigment epithelial cells, causing vision loss in patients with Stargardt disease ( Tornabene et al, 2021 ). In order to repair the ABCA4 mutation, the ABCA4 gene is split into two; and each half is linked to split inteins which are separated, loaded onto AVV vectors, and delivered to one-month-old Abca4 −/− mice subretinally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation